Ketamine Induces Lasting Antidepressant Effects by Modulating the NMDAR/CaMKII-Mediated Synaptic Plasticity of the Hippocampal Dentate Gyrus in Depressive Stroke Model - Idriss Ali Abdoulaye; Shan-shan Wu; Enkhmurun Chibaatar; Da-fan Yu; Kai Le; Xue-jin Cao; Yi-jing Guo (Neural Plasticity)
Background. Ketamine has been shown to possess lasting antidepressant properties. However, studies of the mechanisms involved in its effects on poststroke depression are nonexistent. Methods. To investigate these mechanisms, Sprague-Dawley rats were treated with a single local dose of ketamine after middle cerebral artery occlusion and chronic unpredicted mild stress. The effects on the hippocampal dentate gyrus were analyzed through assessment of the N-methyl-D-aspartate receptor/calcium/calmodulin-dependent protein kinase II (NMDAR/CaMKII) pathway, synaptic plasticity, and behavioral tests. Results. Ketamine administration rapidly exerted significant and lasting improvements of depressive symptoms. The biochemical analysis showed rapid, selective upregulation and downregulation of the NMDAR2-β and NMDAR2-α subtypes as well as their downstream signaling proteins β-CaMKII and α-phosphorylation in the dentate gyrus, respectively. Furthermore, the colocalization analysis indicated a significant and selectively increased conjunction of β-CaMKII and postsynaptic density protein 95 (PSD95) coupled with a notable decrease in NMDAR2-β association with PSD95 after ketamine treatment. These changes translated into significant and extended synaptic plasticity in the dentate gyrus. Conclusions. These findings not only suggest that ketamine represents a viable candidate for the treatment of poststroke depression but also that ketamine’s lasting antidepressant effects might be achieved through modulation of NMDAR/CaMKII-induced synaptic plasticity in key brain regions.